Between Social Structures and Individual Agency: Resistance to Same-Clan Marriage Prohibition in Mandailing Batak Society - Mohammad Fauzan Ni'ami; Muhammad Yusuf Rangkuti; Rafif Zufar Hernowo (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2026)
This study stems from the appearance of same-clan marriage practices among the Mandailing Batak Muslim, even though such practices are strictly prohibited under customary law. However, such practices are often normatively understood as violations and abuses of custom, without considering the perspectives and motivations of each actor. This study specifically aims to examine the prohibition of same-clan marriage and explain how the interaction between social structures and individual agency shapes such resistance within the Mandailing Batak community. This is an empirical study employing a socio-legal approach. Using Anthony Giddens’ theory of structuration, this study aims to reveal the factors influencing individual agency and the interaction between structure and agency in explaining the emergence of resistance to the customary prohibition against same-clan marriage. The findings reveal that structure manifests as customary law, values and beliefs, and sanctions for those who marry within the same clan among the Mandailing Batak people. Meanwhile, individual agency manifests as perspectives rooted in love (affection), family pressure, migration, modernization, and knowledge of the law and Islam. In this context, the interaction or duality between structure and individual agency results in open resistance. This study contributes by offering a new perspective on individual agency within indigenous communities by demonstrating that individuals are not entirely passive within social structures but can influence, navigate, and even challenge customary legal practices. This study argues that the stronger the social structure, the stronger the resistance.